2020
DOI: 10.22146/jieb.54292
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tax Education in Higher Education on Tax Knowledge and Its Effect on Personal Tax Compliance

Abstract: Introduction: This study has 3 (three) objectives. First, to analyze whether tax education in higher education influences individual tax compliance through increased tax knowledge. Second, to explore the implementation of tax education in universities. Third, to identify cooperation carried out by universities and the Directorate General of Taxation in order to improve individual tax compliance. The research method used in this study is a mixed-method. Background Problems: In previous studies educational varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 3 publications
1
33
0
8
Order By: Relevance
“…On the other hand, H2 regarding tax education programmes provided by the tax authority is not supported. The result is found to be inconsistent with previous studies under similar element (Mohani 2001;Park & Hyun 2003;Loo et al 2009;Marziana et al 2010;Mohd Rizal 2010;Marhaini 2012;Norzilah et al 2016;Nuridayu et al 2017;Yee et al 2017;Alm 2018;Kwok & Yip 2018;Kurniawan 2020). The result implies that IRBM needs to improve their tax education programme as the current programme found to be insufficient to influence tax compliance.…”
Section: Multiple Regression Analysismentioning
confidence: 63%
See 1 more Smart Citation
“…On the other hand, H2 regarding tax education programmes provided by the tax authority is not supported. The result is found to be inconsistent with previous studies under similar element (Mohani 2001;Park & Hyun 2003;Loo et al 2009;Marziana et al 2010;Mohd Rizal 2010;Marhaini 2012;Norzilah et al 2016;Nuridayu et al 2017;Yee et al 2017;Alm 2018;Kwok & Yip 2018;Kurniawan 2020). The result implies that IRBM needs to improve their tax education programme as the current programme found to be insufficient to influence tax compliance.…”
Section: Multiple Regression Analysismentioning
confidence: 63%
“…Besides, tax knowledge will also lead to a rational decision such as to comply with the specified time required by the tax law (Marziana et al 2010;Park & Hyun 2003). Overall, previous studies confirmed that taxpayers with better tax knowledge are more willing to comply with the law since they pose with a good level of understanding as a result of being exposed to their tax responsibilities during tax education programmes (Mohani 2001;Park & Hyun 2003;Loo et al 2009;Marziana et al 2010;Mohd Rizal 2010;Marhaini 2012;Norzilah et al 2016;Nuridayu et al 2017;Yee et al 2017;Alm 2018;Kwok & Yip 2018;Kurniawan 2020). Therefore, our second hypothesis is:…”
Section: Tax Education Programmementioning
confidence: 89%
“…Employers can play a significant role to promote and encourage Muslim taxpayers to pay zakat; not only to ensure they perform their duties as a Muslim but also to reduce their financial burden. Other than that, tax education should be introduced to all higher education students because improvement in tax education has a significant effect on tax compliance (Kurniawan, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Kasipillai, Aripin and Amran (2003) suggest that universities should provide basic information materials on taxation to all students. The aim of these policies is to increase students' tax awareness and thus their level of tax literacy (Kurniawan, 2020). The apparent positive effect of tax education in secondary education on increasing taxpayer tax literacy has been identified in research by Kurniawan (2020) or Palil and Mustapha (2011) who also find that a higher level of tax knowledge has a significant effect on taxpayer compliance.…”
Section: Introductionmentioning
confidence: 98%
“…The aim of these policies is to increase students' tax awareness and thus their level of tax literacy (Kurniawan, 2020). The apparent positive effect of tax education in secondary education on increasing taxpayer tax literacy has been identified in research by Kurniawan (2020) or Palil and Mustapha (2011) who also find that a higher level of tax knowledge has a significant effect on taxpayer compliance. To this, Latiff, Noordin, Omar and Harjito (2005) add that it is certainly important to promote taxpayer education, but it is also necessary for taxpayers themselves to show an interest in tax knowledge.…”
Section: Introductionmentioning
confidence: 98%